Translation of Cultural Aspects in Indonesian Folklore Nyai Anteh Sang Penunggu Bulan by Students of the German Department UM - Kezia Gracela Widya Lawalata; Rosyidah Rosyidah (Universitas Negeri Malang, 2022)
This study aims to describe the translation of cultural aspects folklore